Study about Digital Detector on Bureau Classification of Indonesia: A Case Study of Self-unloading Vessel Bought from China - Danny, F.; Muswar, M.; Fridolini, F. (Technological Innovation in Engineering Research Vol. 8, 2022)
The mandated ship classification that was used in this study's descriptive techniques and literature data was done for safety reasons and served as one of the metrics for determining whether or not sailing was worthwhile. The technical specifications and calculations of hull construction, stability, electrical machinery, and the supporting systems of the vessel operating systems, such as boilers, steering system, and others, are more the emphasis of classification standards. In the implementation of the principle of sabotage (Presidential Instruction Number 5 in 2005) about the empowerment of the cruise industry nationwide, the Government issued new rules for the shipping industry operating in Indonesia the fulfilment of class acceptance requirements for foreign vessels that have been purchased and operating in the Indonesian territory becomes an important concern, so that all ships sailing within the territory of Indonesia have been registered in the Indonesian Classification Bureau, its consequences are to be classed in the domestic ship classification and in this case is the Bureau Classification of Indonesia (BKI). Due to the fact that this study involves foreign ships bought in China, it is necessary to complete a classification at the Indonesian Classification Bureau (BKI) and meet the requirements for finished shipbuilding class acceptance procedures before BKI issues a Temporary Classification Certification and Temporary Load Line Certificate for foreign ships that are bought and later operated in Indonesian waters.